The transuranium people - Hoffman, Darleane C. (Imperial College Press, 2000)
In this volume, three pioneering investigators provide an account of the discovery and investigation of the nuclear and chemical properties of the 20 known transuranium elements. The neutron irradiation of uranium led to the discovery of nuclear fission in 1938 and then to the first transuranium element, neptunium (atomic number 93) in 1940. Plutonium (94) quickly followed and the next nine elements completed the actinide series by 1961. Investigation of the chemical properties of actinides was followed more recently by chemical studies of the first three transactinides - rutherfordium (104), hahnium (105) and seaborgium (106).